The Road to Gaza, Part II: The Capitalization of Everything - Shimshon Bichler; Jonathan Nitzan (Real-World Economics Review, 2024)
Our recent article on `The Road to Gaza' examined the history of the three supreme-God churches and the growing role of their militias in armed conflicts and wars around the world. The present paper situates these militia wars in the broader vista of the capitalist mode of power. Focusing specifically on the Middle East, we show the impact these militia wars have on relative oil prices and differential oil profits and explain how the wars themselves, those who stir them and the subjects that fight them all get discounted into capitalized power.
Keywords: P00; P1; P12; P18; H56; N4; 330; capitalization; church; corporation; differential accumulation; dominant capital; energy conflicts; Gaza; Middle East; militia; oil; OPEC; religion; war; Weapondollar-Petrodollar Coalition